PENGARUH INOVASI PRODUK DAN STRATEGI PEMASARAN TERHADAP PENDAPATAN PADA KELOMPOK BINAAN INDONESIA POWER DI DESA RANUKLINDUNGAN GRATI PASURUAN - Anggraini, Pipit; Sutikno, Bambang; Oktafiah, Yufenti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
Product innovation and marketing strategy are considered important factors that can increase the competitiveness and income of the target group. Problems that occur in groups assisted by PT. PLN Indonesia Power Generation Unit (PGU) Grati in Ranuklindungan Village is located at an unstable income that even decreases every month. This research aims to analyze the influence of Product Innovation and Marketing Strategy on Income in the Indonesia Power Assisted Group in Ranuklindungan Village, Grati, Pasuruan. The type of research used in this research is quantitative. The population used is members of the Indonesia Power assisted group in Ranuklindungan Grati Pasuruan Village. The sampling technique used a saturated sampling technique using a sample of 37 respondents. The analysis used is research instrument testing in the form of validity and reliability testing, descriptive analysis, classical assumption testing, multiple linear regression analysis, hypothesis testing and determinant coefficient testing. The research results of the Product Innovation variable partially have a significant effect on Income in the Indonesia Power assisted group in Ranuklindungan Grati Pasuruan Village, this means that Product Innovation plays a very important role in Income. And the Marketing Strategy variable partially has a significant effect on Income in the Indonesia Power assisted group in Ranuklindungan Grati Pasuruan Village, this means that the Marketing Strategy variable also plays a very important role in Income. The determinant coefficient (R2) obtained a value of 0.862 which shows that the influence of Product Innovation and Marketing Strategy can influence Revenue by 86.2%. while other variables outside the scope of the research were 13.8%. Keywords: Product Innovation, Marketing Strategy and Opinion.